Reduction of data size for transmission in localization of mobile robots - Matsumoto, T.; Takahashi, T.; Iwahashi, M.; Kimura, T.; Salbiah, S.; Mokhtar, Norrima (Academic Journals, 2010)
In the SLAM (Simultaneous Localization and Mapping) technology, an environmental map is generated by a mobile robot. When it results in failure, it is necessary to inspect the scene. This localization and browsing require transmission of video signal to a remote place. In the system in this paper, an indoor mobile robot has two cameras. One is the "upward" which captures scenery of ceiling. The other is "forward" for scenery in front of the robot. Video signals from the cameras are encoded and transmitted from the robot to a remote server. It causes a problem that data size is too huge to be transmitted. To cope with this problem, the Functionally Layered Coding (FLC) was reported. In the existing FLC, visual motions are estimated by using the rotation invariant phase only correlation (RI- POC) technique. It can estimate two kinds of motions - translation and rotation. However, it requires doubled computational complexity and many components to be transmitted. In this paper, we analyze relation between kinetic movements of a robot and visual motions observed in videos, and propose to replace RI- POC by a simple POC. It was confirmed that the proposed method reduced data size for transmission to 61.6.